Evaluation of the Effectiveness of a Psychoeducational Intervention in Treatment-Naïve Patients with Antidepressant Medication in Primary Care: A Randomized Controlled Trial - R. Casañas; R. Catalán; R. Penadés; J. Real; S. Valero; MA. Muñoz; LL. Lalucat-Jo; M. Casas (The Scientific World Journal)
Background. There is evidence supporting the effectiveness of psychoeducation (PE) in patients with symptoms of depression in primary care (PC), but very few studies have assessed this intervention in antidepressant-naïve patients. The aim of this study is to assess the effectiveness of a PE program in these patients, since the use of antidepressant (AD) medication may interfere with the effects of the intervention. Methods. 106 participants were included, 50 from the PE program (12 weekly 1.5-hour sessions) and 56 from the control group (CG) that received the usual care. Patients were assessed at baseline and at 3, 6, and 9 months. The main outcome measures were the Beck Depression Inventory (BDI) and remission based on the BDI. The analysis was carried out on an intention-to-treat basis. Results. The PE program group showed remission of symptoms of 40% (P=0.001) posttreatment and 42% (P=0.012) at 6 months. The analysis only showed significant differences in the BDI score posttreatment (P=0.008; effect size Cohen’s d′=0.55). Conclusions. The PE intervention is an effective treatment in the depressive population not treated with AD medication. Before taking an AD, psychoeducational intervention should be considered.